A new strategy proposal to monitor ray fins landings in south‐east Brazil. Issue 1 (9th December 2019) - Almeida Marques, Rebeca; Guimarães Julio, Tainá; Sole‐Cava, Antonio Mateo; Vianna, Marcelo
Abstract: Statistical fisheries data are usually obtained during landings, through rapid fish classification and their categorization under the trade names given to species or groups of species. However, species classification is often difficult, particularly concerning elasmobranchs whose fins and heads have been removed, leading to labelling errors. The aim of this paper is to identify the ray species composition landed in south‐east Brazil, providing identification strategies to support a plan for more efficient labelling and management. Samples were obtained from artisanal fleet landings, between November 2012 and May 2014. For taxonomic identification of whole or processed animals ( n = 279, belonging to 10 species), morphological, metric, and molecular techniques were employed. The common name used by fishermen was more related to the location where they lived than the fishing gear used. Morphometric analyses resulted in pectoral fin to length and weight conversion equations of whole individuals for each species, and 10 variables were found to be diagnostic of each genus. A genetic identification, based on sequencing of the mitochondrial genes cytochrome b and cytochrome oxidase I, was applied to verify morphological identification. A dichotomous key that allowed ray identification at the species level from pectoral fin morphology was developed. The approach was field tested and deemed adequate, leading to a robust monitoring strategy for estimating the biomass of specific landed rays.